al- Muḥaddiṯ al-fāṣil baina 'r-rāwī wa-'l-wāʿī - Rāmahurmuzī, al-Ḥasan Ibn-ʿAbd-ar-Raḥmān ar- -971 (Silsilat Iṣdārāt an-Nāšir al-Mutamaiyiz, 2017)
Hadith; evidences, authority; criticism, interpretation, etc